The prognostic value of preoperative peripheral blood inflammatory biomarkers in extrahepatic cholangiocarcinoma: a systematic review and meta-analysis - Zeng, Di; Wang, Yaoqun; Wen, Ningyuan; Lu, Jiong; Li, Bei; Cheng, Nansheng (Frontiers in Oncology, 2024)
Background: Recent evidence indicates that inflammation plays a major role in the pathogenesis and progression of CCA. This meta-analysis seeks to evaluate the prognostic implications of preoperative inflammatory markers, specifically NLR, PLR, and LMR, in patients with eCCA. By focusing on these preoperative biomarkers, this study aims to provide valuable insights into their prognostic value and potential utility in clinical practice. Methods: For this analysis, comprehensive searches were conducted in PubMed, Embase, and Web of Science databases from inception to May 2024. The primary outcomes of interest focused on the association between the levels of NLR, PLR, and LMR and the prognosis of eCCA patients. Statistical analyses were conducted using STATA 17.0 software. Results: The meta-analysis, involving 20 retrospective studies with 5553 participants, revealed significant correlations between preoperative biomarkers and the prognosis of eCCA patients. Elevated NLR, PLR, and decreased LMR levels were extensively studied regarding overall survival (OS) in eCCA patients. Elevated NLR was an independent predictor of poor OS (HR 1.86, p < 0.001), similar to elevated PLR (HR 1.76, p < 0.001), while decreased LMR predicted poor OS (HR 2.16, p < 0.001). Subgroup analyses based on eCCA subtypes and curative surgery status showed consistent results. Conclusions: In conclusion, our study emphasizes the clinical significance of assessing NLR, PLR, and LMR preoperatively to predict patient prognosis. Elevated NLR and PLR values, along with decreased LMR values, were linked to poorer overall survival (OS). Large-scale prospective cohort studies are required to confirm their independent prognostic value in eCCA.